A Twitter network analysis of European museums. (2nd November 2021) - Kydros, Dimitrios; Vrana, Vasiliki
ABSTRACT: Increasing numbers of museums use Twitter to attract visitors, engage effectively with them and facilitate the construction and strengthening of communities, where visitors are creating their own authentic, trustworthy content. This paper creates and analyzes the network of Twitter users that talk about top European museums (based on TripAdvisor's' ranking) and produces some semantic analysis of the actual content of tweets. Findings show that there is not a real correlation between traffic in Twitter and the corresponding TripAdvisor's' ranking. There is an active discussion between users, sometimes involving different museums, while official accounts play an important role in information circulation. Word adjacencies over all connected tweets revealed general topics of discussions. A careful assessment of the discussions could boost public interest, promote the reputation of the museum and help the museum make improvements to deliver better visitor experiences that surpass their expectations.